Analysis of the Influence of Family Economy and Student Motivation on the Learning Outcomes - Yusrianto Sholeh (Journal of Practice Learning and Educational Development, 2025)
This research about the influence of family economics and student motivation on learning outcomes is the main objective of this research, as a form of our concern as researchers for everyone to be able to educate that the variables we research have an influence between variables. The research data consisted of 30 respondents, at the Al-Kahfi Gangseyan Sepulu Vocational School, the sampling technique used the accidential sampling method, while the data analysis technique used multiple linear regression using SPSS version 23. The test results from this research show that the validity test results on The reliability test value of Crombach alpha at (X1) is 0.636 (X2) is 0.622 and at (Y) is 0.696, so the reliability test is said to be reliable because the Crombach alpha value is greater than the r table, because the r table value itself is 0.361. The normality test of the significant value on the Student Motivation variable (X2) produced (Asymp.sig = 0.192) is greater than the alpha value (a=0.05). So it can be concluded that the data from the Student Motivation variable (X2) is normally distributed. Meanwhile, the T test produces a value for the T calculated variable (X1) of 0.740, while the T sig value is 0.466 and (X2) 6.442, while the T sig value for the variable (X2) is 0.000, so the variables X1 and X2 are said to be significant because the calculated T value > T Sig.It can be concluded that variable (X1) family economics has a positive and significant effect on learning outcomes and (X2) student motivation has a significant effect on student learning outcomes (Y)